Probabilistic linkage of national immunisation and state-based health records for a cohort of 1.9 million births to evaluate Australia's childhood immunisation program. (2017) - Gidding, Heather F; McCallum, Lisa; Fathima, Parveen; Snelling, Thomas; Liu, Bette; Klerk, Nicholas de; Blyth, Christopher C; Sheppeard, Vicky; Andrews, Ross M; Jorm, Louisa; McIntyre, Peter B; Moore, Hannah C
No abstract available